Hubungan Terpaan Iklan Ramayana Versi Kasidah di YouTube dan Tingkat Pendapatan dengan Minat Beli di Ramayana Departemen Store - Burhanudin Ilham Wibawa, Muhammmad; Nur Suryanto Gono, Joyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
YouTube viewers in Indonesia have produced more television viewers. Not surprisingly, manufacturers began to use YouTube as their product promotion field. One brand that uses the media is the Ramayana Department Store. Through the kasidah version of the ad, Ramayana tries to convey the superiority of their products on YouTube. The ad has been watched as many as 16,250,632 times and liked 109,000 people. Viewers these ads increased by 154% compared to previous year's ads on YouTube. In addition, per capita income in Indonesia also increased. Supposedly, with the higher ad exposure, and the higher income level, the higher the purchase intention of someone. However, in fact, Ramayana Department Store has not become the most popular brand on Indonesia. The purpose of this study was to determine the corelation between ad exposure of Ramayana kasidah version on YouTube, and income level with purchase intention on Ramayana Department Store. The theory used today is the Advertising Exposure Theory and social kategory. This research is a quantitative study with an explanatory type. Researchers use non-probability sampling technique with a sample of 60 people aged 19-34 years in the city of Semarang who have been exposed to the Kasidah version of the Ramayana ad on YouTube. Based on the hypothesis test performed using Kendall's Tau analysis, it shows that there is a positive relationship on the ad exposure variables with the purchase intention on Department Store's Ramayana with a significance 0,000 and corellation coefficient 0.689. The income level variable with the Ramayana Department Store is also positively associated with a significance 0.00 and a corellation coefficient 0.568. The conclusion of this study is there is positive relationship between Ramayana ad kasidah version on YouTube and income level with purchase intention on Ramayana Department Store. With these results, it is recommended for the Ramayana Department Store to advertise more often in other media as well with a shorter duration using endorsers that are better known to the public.